The Relationship Between ICU Nurse Burnout Levels and the Quality of Nursing Care for Critically Ill Patients - Novi Yulianti; Rahmat Pannyiwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
ABSTRACT Burnout is a condition of physical, emotional, and mental exhaustion often experienced by healthcare workers due to high work pressure. Nurses working in intensive care units... Care Unit (ICU) has a high risk of experiencing burnout due to complex work demands and responsibilities in caring for critical patients. Burnout in nurses can affect the quality of nursing care provided to patients. This study aims to determine the relationship between the burnout level of ICU nurses and the quality of nursing care in critical patients. The study used an analytical design with a cross-sectional approach . The study sample consisted of 50 ICU nurses selected using a total sampling technique. Burnout was measured using the Maslach Burnout Inventory (MBI) questionnaire, while the quality of nursing care was assessed through a standard nursing service observation sheet. Data analysis used the chi-square test . The results showed that nurses with high burnout levels had lower quality of nursing care than nurses with low burnout levels. The statistical test results showed a p value = 0.021 (p < 0.05). It was concluded that there is a significant relationship between the burnout level of ICU nurses and the quality of nursing care in critical patients. Keywords: Burnout, ICU Nurses, Quality of Nursing Care, Critical Patients